Perspectives On Quality of Care and Satisfaction Among Geriatric Patient-Tourist: Case Study in Klang Valley, Malaysia - Nur Ida Fatihah Che Shalifullizam; Rahmat Hashim; Sree Kala A/P Kunju Raman Nair (Indonesian Journal of Social Research (IJSR), 2021)
Tourism is seen as a fast and booming industry in this age and is being conducted for a variety of purposes. Notably, the world medical tourism market has grown rapidly over the past decade and is expected to grow at an exponential rate, where one of the clear goals of geriatric medicine is to ensure that older people receive better healthcare, specifically, for high-quality patient care. This study identifies the Stimulus Organism Response (SOR) with the injecting of the Donabedian theory that influences the satisfaction of international, domestic, as well as foreign geriatric patient-tourists. Based on the Stimulus Organism Response (SOR) framework and the injecting of the Donabedian theory (2005) with the application of the non-probability sampling techniques that was used, an online questionnaire had been distributed among selected hospitals in the Klang Valley. Accordingly, the Smart PLS 3.3.2 was used to analyse the data for this study using the (SEM) approach, and from the online questionnaire that had been distributed, 139 data were used for further analysis. The findings showed that all the hypotheses (H1-H3) were supported. The expectation has positive effects leaning towards the confirmation and geriatric patient satisfaction; the confirmation is a mediator between expectation and the geriatric patient-tourist satisfactic.